2004
DOI: 10.1177/000992280404300408
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Pediatrician Communication about Complementary and Alternative Medicine Use for Children

Abstract: Anonymous self-report surveys of a convenience sample of caregivers accompanying children to the pediatrician for acute or well visits at 4 pediatric practices in the Washington, DC area from July through November 1998 were evaluated. Three hundred seventy-eight (85%) of 443 caregivers approached participated. The 348 surveys completed by parents (92%) were analyzed. As previously reported, in this sample 21% of parents used complementary and alternative medicine (CAM) for their child. Overall, 53% of parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 24 publications
5
61
3
2
Order By: Relevance
“…205 Evidence that the target symptoms are interfering substantially with learning/academic progress, socialization, health/safety (of the patient and/or others around him or her), or quality of life Suboptimal response to available behavioral interventions and environmental modifications Research evidence that the target behavioral symptoms or coexisting psychiatric diagnoses are amenable to pharmacologic intervention Choose a medication on the basis of Likely efficacy for the specific target symptoms Potential adverse effects Practical considerations such as formulations available, dosing schedule, cost, and requirement for laboratory or electrocardiographic monitoring Informed consent (verbal or written) from parent/guardian and, when possible, assent from the patient Establish plan for monitoring of effects Identify outcome measures Discuss time course of expected effects Arrange follow-up telephone contact, completion of rating scales, reassessment of behavioral data, and visits accordingly Outline a plan regarding what might be tried next if there is a negative or suboptimal response or to address additional target symptoms Change to a different medication Add another medication to augment a partial or suboptimal therapeutic response to the initial medication (same target symptoms) Add a different medication to address additional target symptoms that remain problematic Obtain baseline laboratory data if necessary for the drug being prescribed and plan appropriate follow-up monitoring Explore the reasonable dose range for a single medication for an adequate length of time before changing to or adding a different medication Monitor for adverse effects systematically Consider careful withdrawal of the medication after 6-12 mo of therapy to determine whether it is still needed Another recent parent survey found that 52% of the children with an ASD had been treated with at least 1 CAM therapy, compared with 28% of a group of control children without disabilities. 207 Surveys indicate that only 36% to 62% of caregivers who used CAM therapies for their children with ASDs had informed the child's primary care physician, 207,208 although more information on CAM is something that families indicate that they want from their child's primary health care professionals. 209 It is important that health care professionals understand how to evaluate the evidence used to support all treatments, including CAM, psychopharmacologic, and other interventions.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…205 Evidence that the target symptoms are interfering substantially with learning/academic progress, socialization, health/safety (of the patient and/or others around him or her), or quality of life Suboptimal response to available behavioral interventions and environmental modifications Research evidence that the target behavioral symptoms or coexisting psychiatric diagnoses are amenable to pharmacologic intervention Choose a medication on the basis of Likely efficacy for the specific target symptoms Potential adverse effects Practical considerations such as formulations available, dosing schedule, cost, and requirement for laboratory or electrocardiographic monitoring Informed consent (verbal or written) from parent/guardian and, when possible, assent from the patient Establish plan for monitoring of effects Identify outcome measures Discuss time course of expected effects Arrange follow-up telephone contact, completion of rating scales, reassessment of behavioral data, and visits accordingly Outline a plan regarding what might be tried next if there is a negative or suboptimal response or to address additional target symptoms Change to a different medication Add another medication to augment a partial or suboptimal therapeutic response to the initial medication (same target symptoms) Add a different medication to address additional target symptoms that remain problematic Obtain baseline laboratory data if necessary for the drug being prescribed and plan appropriate follow-up monitoring Explore the reasonable dose range for a single medication for an adequate length of time before changing to or adding a different medication Monitor for adverse effects systematically Consider careful withdrawal of the medication after 6-12 mo of therapy to determine whether it is still needed Another recent parent survey found that 52% of the children with an ASD had been treated with at least 1 CAM therapy, compared with 28% of a group of control children without disabilities. 207 Surveys indicate that only 36% to 62% of caregivers who used CAM therapies for their children with ASDs had informed the child's primary care physician, 207,208 although more information on CAM is something that families indicate that they want from their child's primary health care professionals. 209 It is important that health care professionals understand how to evaluate the evidence used to support all treatments, including CAM, psychopharmacologic, and other interventions.…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…13 Also in the published literature about this topic, a survey of parents found that more than 50% had used at least one CAM therapy for their children with ASD. 14 Other surveys indicate that caregivers don't always inform their child's primary care physician about the use of CAM, 15 although more information about CAM is something that families specify that they want from the child's primary healthcare providers. 16 To gain further knowledge and insight regarding CAM use in a community-based autism population, a survey tool was developed to measure the frequency of CAM use and to better understand child-and family-specific characteristics of CAM users.…”
mentioning
confidence: 99%
“…Two-thirds of chronically ill patients use HDS, frequently in conjunction with prescription and over-the-counter medications. However, only 30% discuss their use of HDS with their physician [2,[18][19][20][21][22][23][24][25][26]28,29].…”
Section: Issues Related To Dietary Supplement Safety and Regulationmentioning
confidence: 99%
“…Physicians rarely identify HDS use among inpatients [2,[18][19][20][21][22][23][24][25][26]28,29]. Few alternative therapies have objective data from well-designed, properly conducted trials to support their use [10].…”
Section: Policy Responses To Herbal Product and Dietary Supplement Usmentioning
confidence: 99%